Focusing the HIV response through estimating the major modes of HIV transmission: a multi-country analysis. (20th November 2012) - Gouws, Eleanor; Cuchi, Paloma
Abstract : Objective: An increasing number of countries have been estimating the distribution of new adult HIV infections by modes of transmission (MOT) to help prioritise prevention efforts. We compare results from studies conducted between 2008 and 2012 and discuss their use for planning and responding to the HIV epidemic. Methods: The UNAIDS recommended MOT model helps countries to estimate the proportion of new HIV infections that occur through key transmission modes including sex work, injecting drug use (IDU), men having sex with men (MSM), multiple sexual partnerships, stable relationships and medical interventions. The model typically forms part of a country-led process that includes a comprehensive review of epidemiological data. Recent revisions to the model are described. Results: Modelling results from 25 countries show large variation between and within regions. In sub-Saharan Africa, new infections occur largely in the general heterosexual population because of multiple partnerships or in stable discordant relationships, while sex work contributes significantly to new infections in West Africa. IDU and sex work are the main contributors to new infections in the Middle East and North Africa, with MSM the main contributor in Latin America. Patterns vary substantially between countries in Eastern Europe and Asia in terms of the relative contribution of sex work, MSM, IDU and spousal transmission. Conclusions: The MOT modelling results, comprehensive review and critical assessment of data in a country can contribute to a more strategically focused HIV response. To strengthen this type of research, improved epidemiological and behavioural data by risk population are needed.